2010
DOI: 10.1007/s11127-010-9654-1
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic and partisan election cycles in Brazil: new evidence at the municipal level

Abstract: Political cycles, Brazilian municipalities, Panel data, C23, H72,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0
26

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 26 publications
2
53
0
26
Order By: Relevance
“…The inclusion of population size is used to account for the demand for government services and also for the degree of political accountability, which is thought to be inversely proportional to the size of the electoral district (Porto and Porto (2000)). The age structure of the population (proportion of elderly and young) has become a standard approach in the PBC literature for capturing variations in the demand for government services (Brender and Drazen, 2005;Rose, 2006;Sakurai and Menezes-Filho, 2011;Veiga and Veiga, 2007). 20 Given that fiscal variables usually exhibit persistence over time, the estimations include the first lag of the dependent variable as an additional regressor.…”
Section: Empirical Methodologymentioning
confidence: 99%
“…The inclusion of population size is used to account for the demand for government services and also for the degree of political accountability, which is thought to be inversely proportional to the size of the electoral district (Porto and Porto (2000)). The age structure of the population (proportion of elderly and young) has become a standard approach in the PBC literature for capturing variations in the demand for government services (Brender and Drazen, 2005;Rose, 2006;Sakurai and Menezes-Filho, 2011;Veiga and Veiga, 2007). 20 Given that fiscal variables usually exhibit persistence over time, the estimations include the first lag of the dependent variable as an additional regressor.…”
Section: Empirical Methodologymentioning
confidence: 99%
“…While recent research identifies several PBC determinants at the national level 2 , there is a growing literature considering political cycles at the local level where greater homogeneity in government structure, available policy instruments (Veiga and Veiga, 2007a) and uniformity in electoral rules and dates (Sakurai and Menezes-Filho, 2011) are present. For instance, Blais and Nadeau (1992) show that in Canada provincial governments' spending on social services and infrastructure construction increases during election years.…”
mentioning
confidence: 99%
“…Likewise, Sakurai and Menezes-Filho (2011) test for opportunistic and partisan cycles in Brazilian municipalities. In particular, their results show that elections have a positive impact on total and current expenditures and a negative impact on local tax revenues.…”
mentioning
confidence: 99%
“…3 Veiga and Veiga (2007), Drazen and Eslava (2010), Aidt et al (2011) and Sakurai and Menezes-Filho (2011) also found political opportunism at aggregated and disaggregated levels of public expenditures but restricted to the municipal level of government. 4 In general, empirical evidence points out that partisan behaviour seems to be more recurrent in developed countries (see Alesina et al, 1992Alesina et al, , 1997.…”
Section: Discussionmentioning
confidence: 94%